A Photoreducible Copper(II)‐Tren Complex of Practical Value: Generation of a Highly Reactive Click Catalyst. Issue 48 (14th October 2013) - Harmand, Lydie; Lambert, Romain; Scarpantonio, Luca; McClenaghan, Nathan D.; Lastécouères, Dominique; Vincent, Jean‐Marc
Abstract A detailed study on the photoreduction of the copper(II) precatalyst 1 to generate a highly reactive cuprous species for the copper(I)‐catalyzed alkyne‐azide cycloaddition (CuAAC) click reaction is presented. For the photoactive catalyst described herein, the activation is driven by a photoinduced electron transfer (PET) process harnessing a benzophenone‐like ketoprofenate chromophore as a photosensitizer, which is equally the counterion. The solvent is shown to play a major role in the CuII to CuI reduction process as the final electron source, and the influence of the solvent nature on the photoreduction efficiency has been studied. Particular attention was paid to the use of water as a potential solvent, aqueous media being particularly appealing for CuAAC processes. The ability to solubilize the copper‐tren complexes in water through the formation of inclusion complexes with β‐CDs is demonstrated. Data is also provided on the fate of the copper(I)‐tren catalytic species when reacting with O2, O2 being used to switch off the catalysis. These data show that partial oxidation of the secondary benzylamine groups of the ligand to benzylimines occurs. Preliminary results show that when prolonged irradiation times are employed a CuI to Cu0 over‐reduction process takes place, leading to the formation of copper nanoparticles (NPs). Finally, the main objective of this work being the development of photoactivable catalysts of practical value for the CuAAC, the catalytic, photolatent, and recycling properties of 1 in water and organic solvents are reported.